Association of brain‐derived neurotrophic factor (BDNF) Val66Met polymorphism with early‐onset bipolar disorder. (3rd September 2015) - Nassan, Malik; Croarkin, Paul E; Luby, Joan L; Veldic, Marin; Joshi, Paramjit T; McElroy, Susan L; Post, Robert M; Walkup, John T; Cercy, Kelly; Geske, Jennifer R; Wagner, Karen D; Cuellar‐Barboza, Alfredo B; et al.
<x xml:space="preserve">Abstract</x> Objectives Brain‐derived neurotrophic factor (BDNF) Val66Met (rs6265) functional polymorphism has been implicated in early‐onset bipolar disorder. However, results of studies are inconsistent. We aimed to further explore this association. Methods DNA samples from the Treatment of Early Age Mania (TEAM) and Mayo Clinic Bipolar Disorder Biobank were investigated for association of rs6265 with early‐onset bipolar disorder. Bipolar cases were classified as early onset if the first manic or depressive episode occurred at age ≤19 years (versus adult‐onset cases at age >19 years). After quality control, 69 TEAM early‐onset bipolar disorder cases, 725 Mayo Clinic bipolar disorder cases (including 189 early‐onset cases), and 764 controls were included in the analysis of association, assessed with logistic regression assuming log‐additive allele effects. Results Comparison of TEAM cases with controls suggested association of early‐onset bipolar disorder with the rs6265 minor allele [odds ratio (OR) = 1.55, p = 0.04]. Although comparison of early‐onset adult bipolar disorder cases from the Mayo Clinic versus controls was not statistically significant, the OR estimate indicated the same direction of effect (OR = 1.21, p = 0.19). When the early‐onset TEAM and Mayo Clinic early‐onset adult groups were combined and compared with the control group, the association of the minor allele rs6265 was statistically significant (OR = 1.30, p = 0.04). Conclusions These preliminary analyses of a relatively small sample with early‐onset bipolar disorder are suggestive that functional variation in BDNF is implicated in bipolar disorder risk and may have a more significant role in early‐onset expression of the disorder.